The Impact of SOA for Achieving Healthcare Interoperability - Daskalakis, S.; Mantas, J. (Methods of Information in Medicine, 2009)
Objectives: The evaluation of a service-oriented prototype implementation for healthcare interoperability.Methods: A prototype framework was developed, aiming to exploit the use of service-oriented architecture (SOA) concepts for achieving healthcare interoperability and to move towards a virtual patient record (VPR) paradigm. The prototype implementation was evaluated for its hypothetical adoption. The evaluation strategy was based on the initial proposition of the DeLone and McLean model of information systems (IS) success [1], as modeled by Iivari [2]. A set of SOA and VPR characteristics were empirically encapsulated within the dimensions of IS success model, combined with measures from previous research works. The data gathered was analyzed using partial least squares (PLS).Results: The results highlighted that system quality is a partial predictor of system use but not of user satisfaction. On the contrary, information quality proved to be a significant predictor of user satisfaction and partially a strong significant predictor of system use. Moreover, system use did not prove to be a significant predictor of individual impact whereas the bi-directional relation between use and user satisfaction did not confirm. Additionally, user satisfaction was found to be a strong significant predictor of individual impact. Finally, individual impact proved to be a strong significant predictor of organizational impact.Conclusions: The empirical study attempted to obtain hypothetical, but still useful beliefs and perceptions regarding the SOA prototype implementation. The deduced observations can form the basis for further investigation regarding the adaptability of SOA implementations with VPR characteristics in the health-care domain.
Keywords: Interoperability; process; assessment-evaluation; IS success model; DeLone and McLean; partial least squares